Pengaruh Pupuk Hayati Jamur Mikoriza Dan Pupuk Rock Phosphate Terhadap Serapan P, Pertumbuhan serta Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) - Rinindra, Riza Jihan; Hermiyanto, Bambang (Berkala Ilmiah Pertanian, 2024)
Application of mycorrhizal fungi biological fertilizers and rock phosphate fertilizers can increase plant P uptake, growth and yield of cayenne pepper (Capsicum frutescens L.). The purpose of this study was to determine the effect of the interaction between mycorrhizal fungi biofertilizer and rock phosphate fertilizer on P uptake, growth and yield of cayenne pepper. The experimental design used was a completely randomized design (CRD) factorial with 2 factors and 3 replications. The first factor was the application of 0 gr (M0), 10 g (M1) and 20 g (M2) mycorrhizal fungal biofertilizers and the second factor was the application of 0 kg rock phosphate fertilizer or the equivalent of 0 g (R0), 150 kg or 1 g (R1) and 300 kg or 2.6 g (M2). The variables observed were plant height, number of fruit planted, fruit fresh weight, plant fresh weight, root volume, root infection, plant dry weight, root shoot ratio and P uptake. The observed data were tested using analysis of variance (ANOVA) and tested further. using Duncan multiple range test (DMRT) at 95% confidence level. The results showed that there was no interaction between the application of mycorrhizal fungi biofertilizers and rock phosphate fertilizers. Application of mycorrhizal fungal biofertilizer (M1) can increase the degree of root infection by 72.22%, the number of fruit planted, fruit fresh weight, plant fresh weight, plant dry weight, root volume, root infection, P uptake and root shoot ratio. Application of rock phosphate fertilizer can also increase the number of fruit plants, plant fresh weight, plant dry weight, root volume and P uptake.